2016
DOI: 10.1007/s00204-016-1831-7
|View full text |Cite
|
Sign up to set email alerts
|

Hepatic transcriptomic alterations for N,N-dimethyl-p-toluidine (DMPT) and p-toluidine after 5-day exposure in rats

Abstract: N,N-dimethyl-p-toluidine (DMPT), an accelerant for methyl methacrylate monomers in medical devices, was a liver carcinogen in male and female F344/N rats and B6C3F1 mice in a 2-year oral exposure study. p-Toluidine, a structurally-related chemical, was a liver carcinogen in mice but not in rats in an 18-month feed exposure study. In this current study, liver transcriptomic data was used to characterize mechanisms in DMPT and p-toluidine liver toxicity and for conducting benchmark dose (BMD) analysis. Male F344… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 49 publications
0
9
0
Order By: Relevance
“…A detailed workflow diagram can be found in Supplementary Figure S1. In addition, a parallel workflow diagram of an example analysis using previously published genomic dose-response data (Dunnick et al, 2017) can be found in Supplementary Figure S2.…”
Section: Discussionmentioning
confidence: 99%
“…A detailed workflow diagram can be found in Supplementary Figure S1. In addition, a parallel workflow diagram of an example analysis using previously published genomic dose-response data (Dunnick et al, 2017) can be found in Supplementary Figure S2.…”
Section: Discussionmentioning
confidence: 99%
“…Raw expression data for livers of male Harlan Sprague Dawley or male F344/N rats exposed orally for 5 days to crude 4-methylcyclohexanemethanol (crude-MCHM), or neat 4-methylcyclohexanemethanol (MCHM), and for kidneys of rats exposed orally to propylene glycol phenyl ether (PPH) were accessed from the Gene Expression Omnibus (GEO) as series GSE75655, GSE75657 and GSE75656, respectively. Hepatic transcriptomics data for F344/N rats exposed orally to N,N-dimethyl-p-toluidine (DMPT) or p-toluidine for 5 days [17] were accessed from the GEO as series GSE100502. All.cel files available for each replicated exposure level and vehicle controls were included in this analysis.…”
Section: Gene Expression Datamentioning
confidence: 99%
“…N,N-dimethyl-p-toluidine (DMPT) is an accelerant for methyl methacrylate monomers in medical devices that has been shown to induce liver carcinogenesis in male and female F344/N rats and B6C3F1 mice in a 2-year oral exposure study. p-toluidine, structurally-related to DMPT, is reportedly a liver carcinogen in mice [17].…”
Section: Gene Expression Datamentioning
confidence: 99%
See 1 more Smart Citation
“…Raw expression data for livers of male Harlan Sprague Dawley or male F344/N rats exposed orally for 5 days to crude 4-methylcyclohexanemethanol (crude-MCHM), or neat 4-methylcyclohexanemethanol (MCHM), and for kidneys of rats exposed orally to propylene glycol phenyl ether (PPH) were accessed from the Gene Expression Omnibus (GEO) as series GSE75655, GSE75657 and GSE75656, respectively. Hepatic transcriptomics data for F344/N rats exposed orally to N,N-dimethyl-p-toluidine (DMPT) or ptoluidine for 5 days [17] were accessed from the GEO as series GSE100502. All .cel files available for each replicated exposure level and vehicle controls were included in this analysis.…”
Section: Gene Expression Datamentioning
confidence: 99%